VD_FINDINFO HC / 2022 / 595 vom 5. September 2022 - VD Tribunal cantonal (2022)
REVENU DÉTERMINANT, CALCUL, PROTECTION DE L'UNION CONJUGALE | 170 al. 2 CC, 176 al. 1 ch. 3 CC, 164 CPC (CH), 308 al. 1 let. b CPC (CH)